Energy dissipation and storage in iron under plastic deformation (experimental study and numerical simulation) (Fracture and Structural Integrity, 2013)
The work is devoted to the experimental and numerical investigation of thermodynamic aspects of the plastic deformation in Armco iron. Dissipation and stored energies was calculated from processed experimental data of the surface temperature obtained by infrared thermography. An original mathematical model describing the process of mesoscopic defects accumulation was used for numerical simulation of the quasistatic loading of iron samples and for calculation of theoretical value of the stored energy. Experimental and modeled values of the stored energy are in a good agreement.
Keywords: Infrared thermography